2011
DOI: 10.1002/bdra.22850
|View full text |Cite
|
Sign up to set email alerts
|

Beta2‐agonists use during pregnancy and the risk of congenital malformations

Abstract: BACKGROUND Treatment of asthma symptoms during pregnancy is crucial for maternal and fetal health. Short‐acting beta2‐agonists (SABA) are frequently used as rescue medications and long‐acting beta2‐agonists (LABA) are used as add‐on controller therapy for asthma during pregnancy. OBJECTIVE The objective of this study was to investigate the association between exposure to SABA and LABA in the first trimester of pregnancy and the risk of congenital malformations among women with asthma. METHODS A cohort of pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 48 publications
2
54
0
1
Order By: Relevance
“…Interestingly, this study, along with a second study from our group,16 were the only studies that measured asthma exacerbations during the first trimester of pregnancy, that is, the most critical period for congenital malformations. Regarding the study populations, the type of health insurance plan was not specified in six of the nine studies,7 8 10 12 14 21 one study was conducted among women with private healthcare insurance,13 and our two studies were conducted among women with public drug insurance only 15 16. The meta-analysis, which included four of the nine studies, reported that asthma exacerbations during pregnancy were not associated with an increased prevalence of congenital malformation 23…”
Section: Introductionmentioning
confidence: 97%
“…Interestingly, this study, along with a second study from our group,16 were the only studies that measured asthma exacerbations during the first trimester of pregnancy, that is, the most critical period for congenital malformations. Regarding the study populations, the type of health insurance plan was not specified in six of the nine studies,7 8 10 12 14 21 one study was conducted among women with private healthcare insurance,13 and our two studies were conducted among women with public drug insurance only 15 16. The meta-analysis, which included four of the nine studies, reported that asthma exacerbations during pregnancy were not associated with an increased prevalence of congenital malformation 23…”
Section: Introductionmentioning
confidence: 97%
“…However, results from a recent meta-analysis suggest that these associations may be chance findings or related to the underlying asthma severity [41] . In contrast, no increase in malformation rate was reported by large database studies [44,50,56,57] . Several studies support the absence of obstetrical or perinatal complications associated with SABA use [44,[58][59][60] .…”
Section: Inhaled Corticosteroidsmentioning
confidence: 84%
“…Several studies support the absence of obstetrical or perinatal complications associated with SABA use [44,[58][59][60] . There are limited observational data on the safety of LABA during pregnancy, although an increase in cardiac malformations has been reported in one study [56] . No difference in perinatal risks has been reported between salmeterol and formoterol [61] .…”
Section: Inhaled Corticosteroidsmentioning
confidence: 97%
“…The asthma diagnostic codes recorded in the RAMQ medical database were shown to be a valid method of identifying patients with asthma [25], and data on medications recorded in the RAMQ prescription database were found to be comprehensive and valid [26]. This cohort has already been used to study the impact of asthma and asthma medications on the health of the mother and the newborn [27][28][29][30].…”
Section: Methodsmentioning
confidence: 99%